Testing self-adaptive applications with simulation of context events - Kakousis, Konstantinos; Paspallis, Nearchos; Papadopoulos, George; Ruiz, Pedro (Electronic Communications of the EASST, 2010)
Modern trends in mobile computing have raised the expectations of usersin terms of such features such as context-awareness and self-adaptiveness. Withsuch capabilities, applications can autonomously sense their context and automate anumber of tasks, effectively reducing the attention required by the end users. Thispaper presents a custom simulation engine, designed to support the testing of applicationsdeveloped using the MUSIC platform. The simulation tool consists ofa platform-independent server module, deployed along with the application, anda client module which is responsible for interpreting and executing the simulationscript. The use of the tool is demonstrated in the scope of the SatMotion application,which is designed to assist satellite antenna installers with specialized functionality.